Why TikTok is a game-changer for modern business? - Amirrudin, Faizatul Akmam; Ahmad Jamil, Norina (Universiti Teknologi MARA, Terengganu, 2024)
Social media platforms are becoming vital tools for businesses in the digital era to engage with their customers, increase brand recognition, and drive business growth. Among these platforms, TikTok stands out as a rapidly growing space that offers unique opportunities for businesses. With its massive and diverse user base, engaging content formats, and powerful algorithm, TikTok provides businesses with numerous benefits that can significantly enhance their marketing and outreach efforts.